Ex Vivo/In vivo gene editing in Hepatocytes using “all-in-one” CRISPR-adeno-associated virus vectors with a self-linearizing repair template - Krooss, Simon; Dai, Zhen; Schmidt, Florian; Rovai, Alice; Fakhiri, Julia; Dhingra, Akshay; Yuan, Qinggong; Yang, Taihua; Balakrishnan, Asha; Steinbrück, Lars; Srivaratharajan, Sangar; Manns, Michael Peter; et al. (iScience, 2020)
Adeno-associated virus (AAV)-based vectors are considered efficient and safe gene delivery systems in gene therapy. We combined two guide RNA genes, Cas9, and a self-linearizing repair template in one vector (AIO-SL) to correct fumarylacetoacetate hydrolase (FAH) deficiency in mice.